Climatic instability before the Miocene Climatic Optimum reflected in a Central European lacustrine record from the Most Basin in the Czech Republic - Matys Grygar, T. (Tomáš); Hošek, M. (Michal); Mach, K.; Schnabl, P. (Petr); Martinez, M. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
The work investigates the extensive freshwater lacustrine deposits of the Most Formation, which formed in the period between 17.7. Ma and ca. 15.9. Ma, in order to describe climate changes just before the Miocene Climatic Optimum (MCO). The Most Basin, an incipient rift within the European Cenozoic Rift System, exhibited a sedimentary environment that was sufficiently stable to preserve orbital signatures of environmental changes. Changes in the mineral composition of the sediments were characterised in terms of variations in their elemental composition, particularly their Al/Si and K/Ti element ratios and Fe, Sr, and Zr elemental abundances, which were efficiently obtained using X-ray fluorescence spectroscopy with a density of 3-4 samples per metre of core (approximately 15-20 samples per precession cycle). The sediments are distinguished by the presence of distinct and correlated horizons (1-10. cm thick) containing Sr, Ba-rich crandallite, a mineral from the aluminium-phosphate-sulphate (APS) group. Chemo-, magneto-, and cyclostratigraphy were used to correlate eight cores with lengths up to 240. m and to date the sediment, discrepancies at scales of up to two precession cycles (each ca. 20. kyr, typically ~. 4. m per cycle) were observed. The primary age model was based on magnetic polarity analysis (5 reversals) and later refined at the metre scale using cyclostratigraphy. We interpret the onset of the basin-wide lacustrine phase in the Most Basin as being a consequence of the enhanced input of fluvial clastic sediment to the former peat swamps during the high-eccentricity period at 17.7-17.55. Ma, i.e., immediately after the initial decay of the East Antarctic ice sheet according to Levy et al. (2016). The most important environmental change recorded by the lacustrine interval in the Most Basin occurred at 16.44. Ma during an eccentricity maximum and is nearly coeval with further shrinkage of the East Antarctic ice sheet.